Activity Test of Squid Ink (Loligo Sp.) As Antibacterial Against Enterococcus Faecalis and Pseudomonas Aeruginosa Bacteria - Valencia Angelina Halim; Sara Rai Faomasi Duha; OK Yulizal; Irza Haicha Pratama (CV. Inara, 2023)
Squid (Loligo sp.) is an invertebrate animal, part of the cephalopod class. The squid has a distinctive black ink fluid for self-defense. Squid ink contains melanin compounds that can be used as an antibacterial. Enterococcus faecalis is a bacterium that causes endodontic infection. While Pseudomonas aeruginosa is a bacterium that causes infection in patients with compromised immune system, and also who using a urinary catheter or intravenous catheter. This study aims to determine whether squid ink can be used as an antibacterial that can suppress the growth of Enterococcus faecalis and Pseudomonas aeruginosa bacteria. This research was conducted with experimental method, true experimental Post-Test Only Control Group research design. The research by using squid ink was carried out by inserting extract with various concentration (20%, 40%, 60%, 80% and 100%) into a petri dish which containing bacterial culture. The final showed that between concentrations of 20%, 40%, 60%, 80% and 100% were no clear zones, which had been repeated 3 times against Enterococcus faecalis and Pseudomonas aeruginosa bacteria. From the results obtained, it can be concluded that there is no bacterial inhibition caused by squid ink against Enterococcus faecalis and Pseudomonas aeruginosa.